Strategi Coping Player Mobile Legends Dalam Menghadapi Tindakan Verbal Abuse - Putri, Pillar Emeraldayanti; Oktaviana, Mimbar (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2024)
This qualitative psychological research aims to find out how (1) the form of Verbal Abuse behavior received by male players in the Mobile Legends game (2) the impact of Verbal Abuse received by male players in Mobile Legends, (3) what kind of coping strategies they do to overcome the Verbal Abuse through a phenomenological approach. Data were collected through semi-structured interviews with four male Mobile Legends:Bang-Bang game players. Through the IPA (Interpretative Phenomenological Analysis) method, three main themes were obtained, namely, the experience of Verbal Abuse, the impact of Verbal Abuse, and coping strategies. The first theme explains the process and form of Verbal Abuse received by men in the Mobile Legends game. The second theme describes the decline in performance, self-confidence, and negative emotion s as an impact of Verbal Abuse. The third theme displays the coping strategies used by male players. From this study it can be concluded that the four participants can deliver the problems they have through coping strategies